Tổng hợp điện hóa và đặc tính của nanocompozit nền poly(Ani/o-Tol) với Fe2O3 nano - An, Trần Văn; Quế, Lê Xuân; Vỹ, Uông Văn (Vietnam Journal of Chemistry, 2015)
PANi-POT/α-Fe2O3 (PATF) nanocomposites were synthesized by electrochemical method on 316 stainless steel in 0.5 M sulfuric acid solution, with aniline/o-toluidine weight ratios 10/0, 9/1, 8/2, 7/3, and 6/4, nano α-Fe2O3 2 % by total weight of monomers. The electrochemical synthesis process were studied by cyclic voltammetry technique (CV), scan rate 50 mV/s, step 5 mV and scan range from -0.2 V to 1 V (SCE). PANi-POT/Fe2O3 nanocomposites were washed with double distilled water to pH = 7, then dried. Properties of the nanocomposite were studied using infrared spectroscopy (IR), thermal gravity analysis (TGA), scanning electron microscopy (SEM) and transmission electron microscopy (TEM).